Systematized review of the innovative Russian IT-solutions for the optimization of drug information in the circulation of medicines - Alexander Sergeevich Belosludtsev, Tatiana Mikhailovna Litvinova (Journal of Applied Pharmaceutical Science, 2023)
An increase in the number of new drug products (DPs) leads to the growth in the associated information. To improve the efficiency of medical and pharmaceutical care, IT-products are created. In this review, we attempt to systematize innovative domestic IT-solutions (dITSs) for the optimization of remote data management of medicines. We have conducted a systematized search over the past 5 years in accordance with the PRISMA framework. eLibrary, CyberLeninka, and Google were utilized as search engines. 18 out of 312 results met the preset criteria. 23 dITSs were extracted. 18 used big data as the main technology, 2 blockchains, 2 artificial intelligence, and 1 continuous acquisition and lifecycle support/product lifecycle management. The innovations point towards the optimization of drug information in medical organizations (16/23) and pharmacies (6/23). In practice, the dITSs are mainly used as databases (10/23), decision support systems (9/23), and automated analytics (6/23). Specific products are infrequently and not comprehensively assessed in scientific papers. It is more efficient to search them on particular sites dedicated to IT-projects. Today’s reasons for the development of the innovative dITSs to optimize information management within the lifecycle of medicines are a necessity to trace each DP and automate the analysis of related information.
Keywords: Drug information, information technologies, telepharmacy, information management, optimization